2018
DOI: 10.1007/s11883-018-0752-8
|View full text |Cite
|
Sign up to set email alerts
|

Associations of 26 Circulating Inflammatory and Renal Biomarkers with Near-Infrared Spectroscopy and Long-term Cardiovascular Outcome in Patients Undergoing Coronary Angiography (ATHEROREMO-NIRS Substudy)

Abstract: Purpose of ReviewThe purpose of this study was to investigate the association of 26 inflammatory biomarkers (acute phase proteins, cytokines, chemokines) and renal markers with coronary lipid core burden index (LCBI) assessed by near-infrared spectroscopy (NIRS) imaging, as well as the association of these biomarkers with long-term cardiovascular outcome.Recent FindingsNIRS-derived LCBI has recently been shown to be an independent predictor of major adverse cardiac events (MACE). However, studies on the associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 25 publications
(37 reference statements)
0
3
0
Order By: Relevance
“…Currently, percutaneous coronary intervention (PCI) is the mainstay of treatment for ACS to restore coronary perfusion and reduce infarct size during acute myocardial ischemia (O’Gara et al, 2013). Nevertheless, ACS patients are prone to recurrent angina and coronary restenosis after PCI due to patients’ predisposing factors, such as myocardial insult, inflammatory disorders, and thrombogenic tendencies (Tsai et al, 2017; Anroedh et al, 2018; Sardu et al, 2018). There is still a lack of highly sensitive and specific approaches to monitor the clinical condition and assess the prognosis of ACS patients.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, percutaneous coronary intervention (PCI) is the mainstay of treatment for ACS to restore coronary perfusion and reduce infarct size during acute myocardial ischemia (O’Gara et al, 2013). Nevertheless, ACS patients are prone to recurrent angina and coronary restenosis after PCI due to patients’ predisposing factors, such as myocardial insult, inflammatory disorders, and thrombogenic tendencies (Tsai et al, 2017; Anroedh et al, 2018; Sardu et al, 2018). There is still a lack of highly sensitive and specific approaches to monitor the clinical condition and assess the prognosis of ACS patients.…”
Section: Introductionmentioning
confidence: 99%
“…Clinically healthy obese people might tend to have higher degrees of B2MG than normal-weight people [35]. Moreover, higher B2MG was correlated with a higher occurrence of major adverse cardiac events [36]. And B2MG as a mediator had been linked to the diet and incident cardiovascular disease, also including all-cause mortality [37].…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] Furthermore, previous studies have reported that pro-inflammatory factors can be used to predict offender plaque characteristics and adverse cardiovascular events after hospital discharge in patients with STEMI. [8][9][10] It was found that TNF-α expression in monocytes is highly correlated with plaque rupture, and TNF-α can be used to predict the occurrence of plaque rupture. 11 Evidence suggested that the IL-1β concentration in STEMI at admission was association with the risk of mortality and recurrent MACE, the increase of IL-1β concentration was the independent predictor of MACE.…”
Section: Introductionmentioning
confidence: 99%